2012
DOI: 10.4102/ojvr.v79i2.454
|View full text |Cite
|
Sign up to set email alerts
|

Towards One Health disease surveillance: The Southern African Centre for Infectious Disease Surveillance approach

Abstract: Africa has the highest burden of infectious diseases in the world and yet the least capacity for its risk management. It has therefore become increasingly important to search for 'fit-for- purpose' approaches to infectious disease surveillance and thereby targeted disease control. The fact that the majority of human infectious diseases are originally of animal origin means we have to consider One Health (OH) approaches which require inter-sectoral collaboration for custom-made infectious disease surveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…Electronic data collection saved time, was less costly, was at least as accurate as standard paper-based questionnaires, and was preferred by experienced paper-based data recorders. These advantages were similar as those advertised in recent applications of Android-based data collection applied to animal health and surveillance of zoonotic diseases [40], [41]. Such systems could be readily applied to other large-scale neglected tropical disease control surveys as well as national initiatives, such as the malaria indicator surveys (MIS), the demographic and health surveys (DHS), the UNICEF multiple indicator cluster survey (MICS), or the regular household surveys done by the health demographic surveillance systems (HDSS) of the INDEPTH network [42]–[44].…”
Section: Discussionsupporting
confidence: 66%
“…Electronic data collection saved time, was less costly, was at least as accurate as standard paper-based questionnaires, and was preferred by experienced paper-based data recorders. These advantages were similar as those advertised in recent applications of Android-based data collection applied to animal health and surveillance of zoonotic diseases [40], [41]. Such systems could be readily applied to other large-scale neglected tropical disease control surveys as well as national initiatives, such as the malaria indicator surveys (MIS), the demographic and health surveys (DHS), the UNICEF multiple indicator cluster survey (MICS), or the regular household surveys done by the health demographic surveillance systems (HDSS) of the INDEPTH network [42]–[44].…”
Section: Discussionsupporting
confidence: 66%
“…Other examples include sharing facilities such as refrigerators for storage of vaccines for humans and for livestock, and vehicles to carry out campaigns against zoonotic diseases. There is some empirical information on such collaborations; Karimuribo et al (2012) found that sometimes animal and health officers in Ngorongoro District, Tanzania, were sharing vaccine storage facilities, especially during times of disease vaccination campaigns when teams of vaccinators were camping in remote rural areas. Although such collaborative activities are undertaken, upscaling the same and undertaking more others is impeded by various barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need to develop sustainable disease control strategy for CCPP in order to promote commercial goat production. Apart from CCPP, a peste des petits ruminants (PPR) has emerged in recent years as the major threat to the small ruminant industry in the country (Karimuribo et al, , 2012. However, it was not encountered in this study.…”
Section: Discussionmentioning
confidence: 85%